Investigation of deformation processes in channels of regulated streams - Baublys, Raimundas (Journal of Environmental Engineering and Landscape Management, 2006)
The paper analyses deformation processes occurring in channels of regulated streams and discusses the reasons of their occurrence. As the study results have shown, the most frequent deformations of regulated streams include the erosion of slopes, accumulation of sediment in the channel, and the overgrowth of the channel with grass, bushes and woody vegetation. Deformations occurring due to the effect of different natural phenomena determined the changes of stream channels in cross‐sectional and longitudinal profiles. Most streams under investigation have not been controlled, i e they are overgrown with thick and high grass vegetation. The paper presents analysis of current situation and discusses different possibilities of the naturalization of regulated streams.Deformacinių procesų sureguliuotų upelių vagose tyrimaiSantrauka. Straipsnyje analizuojami sureguliuotų upelių vagose vykstantys deformaciniai procesai ir aptariamos jų priežastys. Tyrimais nustatyta, kad dažniausios tokių upelių vagų deformacijos yra šlaitų erozija, sąnašų susikaupimas vagoje ir vagos užaugimas žolėmis, krūmais bei miško augalija. Deformacijos, pasireiškusios dėl įvairių gamtinių veiksnių, lėmė upelių vagų skersinių ir išilginių profilių pokyčius. Dauguma tirtųjų upelių buvo neprižiūrimi – apaugę tankia ir aukšta žoline augalija. Analizuojama esama situacija. Aptariamos galimybės natūralizuoti sureguliuotus upelius.Reikšminiai žodžiai: sureguliuoti upeliai, deformacijos, vagos, vingiai, sąnašos, augalija.Исследование деформационных процессов в руслах отрегулированных рекРезюме. Проанализированы деформационные процессы, происходящие в руслах отрегулированных рек, причины их возникновения. Исследованиями установлено, что чаще всего это эрозия откосов, скопление наносов в русле и зарастание русла травой, кустами и лесной растительностью. Деформации, образовавшиеся вследствие различных природных факторов, обусловили изменения поперечных и продольных профилей русел рек. Большинство исследованных рек были неухоженными – заросли густой и высокой трявянистой растительностью. Проанализирована создавшаяся ситуация, обсуждены возможности натурализировать отрегулированные реки.Ключевые слова: отрегулированные реки, деформации, русла, повороты, наносы, растительность.Firstd Published Online: 14 Oct 2010